The Tax Regime Regarding the Taxation of Revenues Obtained Through Contracts of Sport Activities - Lucian CERNUȘCA (CECCAR Business Review, 2021)

(untitled)
This article presents a series of theoretical and practical aspects regarding the taxation of revenues obtained through independent activities conducted under contracts of sport activities. According to the effective legislation, the participants in sport activities can conclude sport activities contracts with sport facilities. The revenues obtained by them is taxed through collection at source and is included in the calculation of the cap used as reference to establish if the beneficiary pays social contributions or not. In order to provide a better understanding of the subject, all these aspects are rendered in this article alongside a case study.